Investigation of the Effect of V-Clamp Band Design Parameters on the Bending and Axial Stiffness of the Flanged Joints - SeyyedAbdolSajjad Borhani; AliAkbar Lotfi neyestanak; Ali davar (International Journal of Advanced Design and Manufacturing Technology, 2019)
The main target of this paper is to obtain an optimum wedge angle for best static and dynamic performance of a V-shaped clamp band separation mechanism. For this purpose, by using the finite element method, the proper 3D model for V-clamp band mechanism has been modelled and analysed in Abaqus/Explicit solver. In order to study the effect of wedge angle on bending and axial stiffness of V-clamp joint, many quasi-static analyses with different wedge angles were accomplished so the relation between wedge angle and axial stiffness of V-clamp joint under symmetric bending loading is extracted. In the next step, dynamic analyses were accomplished so the relation between wedge angle and separation time (duration between trigging moment and the time of disconnecting between flanges and wedged clamps) is extracted. For verification, this project results have been compared with the results of other researches and good agreement is observed. The results show that the optimal wedge angle for obtaining maximum stiffness together with minimum spring back disconnection time for the V-clamp band mechanism is 20˚.